(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2021)
This complex time, lived in isolation between uncertainties and meditations, is also the time of experimentation, searching answers and ideas. The web offers the opportunity to explore numerous information resources and sources of image production, sharing reflections, investigations and projects in which man, space and living are the object of the representations. These are domains where, in real time and with a continuous flow, meaningful images, graphic elaborations concerning cities, architecture, environment and landscape, coming from every corner of the world, converge. The images project on the display not simply representations of the living places, but real visual suggestions, each with different communication and technical methods. They are almost never fluid−looking images, but highly artificial, full of artistic references, allusions, quotations, contaminations, emphasis. The data which crosses those images come from different fields, from biology to economy, from design to cinema, from mathematics to philosophy, to visual culture. During the pandemic, the impulse to resolve the urgent issues of distancing and to rethink the models of human−environment interaction has furthered the use of these sharing platforms, stimulating discussions and debates. The continuous exposure to data, directing in turn the exploration of new regions and the network domains, has made it possible to transform the (visual) experience into the possibility of observing ourselves and the environment, spectators and protagonists of new rituals. The ‘homescape’ is the interesting proposal emerging from the web, which identifies a new ‘total landscape’ in the home environment, self−sufficient, integrated and highly efficient. It appears transformed into an ambiguous space shown through a counter−image, connected to the traditional one in such a way as to suspend, neutralize, reverse the set of relationships which are reflected in it.